Childhood Hearing Health: Educating for Prevention of Hearing Loss - Lacerda,Adriana Bender Moreira (2015)
Introduction The presence of noise in our society has attracted the attention of health professionals, including speech-language pathologists, who have been charged along with educators with developing hearing conservation programs in schools. Objective To describe the results of three strategies for awareness and hearing preservation in first to fourth grades in public elementary schools. Methods The level of environmental noise in classrooms was assessed, and 638 elementary school students from first to fourth grades, 5 to 10 years of age, were audiologically evaluated. After the evaluations, educational activities were presented to children and educators. Results The noise level in the classroom ranged from 71.8 to 94.8 A-weighted decibels. The environment of the classroom was found to promote sound reverberation, which hinders communication. Thirty-two students (5.1%) presented hearing alterations. Conclusion The application of strategies for a hearing conservation program at the school showed that noise is present in the room, and hearing loss, sometimes silent, affects schoolchildren. Students and teachers were aware that hearing problems can be prevented. Avoiding exposure to noise and improving the acoustics in classrooms are essential.